HEROIC NARRATIVES OF GREEK MYTHOLOGY IN THE MOVIES CLASH OF THE TITANS AND WRATH OF THE TITANS: A COMPARATIVE LITERATURE APPROACH - Aji Septiaji; Nanis Regina Choerunnisa; Neci Siti Aliyah; Novi Silvia; Erna Rahmawati (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the representation of heroic narratives in two movies adaptations of Greek mythology, Clash of the Titans (2010) and Wrath of the Titans (2012), through a comparative literature approach and Vladimir Propp's narratology. The main character Perseus is the center of attention in the study of narrative structure because of his role as a mythological hero who faces a series of challenges that are full of values of courage, sacrifice, and determination. Propp's theory is used to identify narrative functions such as dispatch, magical agent, struggle, and transfiguration that appear in both movies. The method used is qualitative with content analysis technique by comparing the stories, characters, and moral messages as well as narrative functions in the two movies with the theme of Greek mythology. The results show that the comparison of the narrative structure of the two movies with the character Perseus has strengths in the dramatic aspects of heroic attitudes in accepting choices and fighting for life so that the integration of heroic material can be adapted to literature learning involving character values. This finding confirms that the narratological approach through comparative literature can be an important pedagogical tool to teach story structures with character values through popular media. This research recommends the utilization of mythological movies in literature learning and character education at various levels of education as a means of strengthening narrative literacy and understanding moral values.